Contribution Factors in Affecting Teacher Performance: Principal Managerial Skills and Work Motivation - Roemintoyo, Roemintoyo; Tauhid, Hasan; Miyono, Noor; Budiarto, Mochamad Kamil (Journal of Education Technology, 2021)
The low performance of teachers is a problem currently faced by educational institutions. In the midst of increasingly complex demands for mastery of competencies, the role of teachers as learning facilitators is important in facilitating students to achieve the competencies needed in the global era like today. Through research that aims to determine the influence of factors that contribute to teacher performance, namely the managerial skills of principals and work motivation, it is hoped that they will be able to become the basis for making policy innovations that can increase teacher productivity and performance. This research is a quantitative research. The research sample consisted of 128 teachers. The questionnaire is the data collection instrument used in research activities. The collected data is then analyzed using a regression formula in accordance with the variables to be tested. The results of this study indicate that there is an effect of principal managerial skills on teacher performance by 77.1%, other factors are motivation, the effect of work motivation on teacher performance is 74.6%, and for the two variables principal managerial skills and work motivation are variable. jointly affect teacher performance by 87.7%. From the findings in this study, it can be concluded that fluctuations in teacher performance fluctuations are strongly influenced by the managerial dynamics of school principals and teacher work motivation. Apart from several other factors that also contribute to improving teacher performance